Silicon nitride powder and its manufacturing method, and method for manufacturing sintered silicon nitride
Patent Information
- Application Number
- JP2020191005
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-17
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2040-11-17
AI Technical Summary
【0018】 本開示によれば、不純物を低減することによって、高い熱伝導率と優れた高温強度を兼ね備える窒化ケイ素焼結体を製造することが可能な窒化ケイ素粉末を提供することができる。また、このような窒化ケイ素粉末を製造することが可能な窒化ケイ素粉末の製造方法を提供することができる。また、高い熱伝導率と優れた高温強度を兼ね備える窒化ケイ素焼結体を製造することが可能な窒化ケイ素焼結体の製造方法を提供することができる。
Smart Images

Figure 0007640249000003 
Figure 0007640249000001 
Figure 0007640249000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a silicon nitride powder and a method for producing the same, and a method for producing a silicon nitride sintered body. [Background technology]
[0002] Silicon nitride is a material that is excellent in strength, hardness, toughness, heat resistance, corrosion resistance, thermal shock resistance, etc. For this reason, the use of silicon nitride sintered bodies as insulating substrates for machine parts such as gas turbines, turbo rotors, and valves, and power modules for automobiles, machine tools, etc. is being considered. Silicon nitride sintered bodies used for these applications are required to have a dense and homogeneous structure. In order to produce such silicon nitride sintered bodies, a technology for providing a high-purity and homogeneous silicon nitride powder is being considered.
[0003] Known methods for synthesizing silicon nitride powder include a direct nitridation method (direct reaction method) in which metal silicon powder is nitrided in a mixed atmosphere of hydrogen gas or ammonia gas and nitrogen gas, a reduction nitridation method of silica powder, and an imide decomposition method. Patent Document 1 proposes a method for producing silicon nitride powder with a high content of α-type Si3N4. Patent Document 2 proposes the production of silicon nitride powder with fewer impurities by the imide decomposition method. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 7-81910 [Patent Document 2] JP 2000-302421 A Summary of the Invention [Problem to be solved by the invention]
[0005] Silicon nitride sintered bodies are sometimes used in high-temperature environments, and therefore are required to have excellent strength at high temperatures (high-temperature strength). When used at high temperatures, they are also required to have excellent heat dissipation properties. In order to improve high-temperature strength and heat dissipation properties, it is considered necessary to make the silicon nitride sintered body dense and reduce the amount of impurities. Factors that affect the densification and amount of impurities in silicon nitride sintered bodies are thought to be the impurities contained in the raw material, i.e., silicon nitride powder, and the agglomeration of the silicon nitride powder.
[0006] The present disclosure provides a silicon nitride powder capable of producing a silicon nitride sintered body having both high thermal conductivity and excellent high-temperature strength. It also provides a method for producing a silicon nitride powder capable of producing such a silicon nitride powder. It also provides a method for producing a silicon nitride sintered body capable of producing a silicon nitride sintered body having both high thermal conductivity and excellent high-temperature strength. [Means for solving the problem]
[0007] A method for producing silicon nitride powder according to one aspect of the present disclosure is a method for producing silicon nitride powder using a raw material powder containing a silicon source, comprising: a first step of heating the raw material powder for 50 hours or more at a temperature Ta [°C] that satisfies the following formula (1), where Tm [°C] is the coalescence temperature of the silicon source, to obtain a calcined product containing silicon nitride; and a second step of heating the calcined product for 20 hours or less at a temperature Tb [°C] that satisfies the following formula (2), to obtain a fired product containing silicon nitride. The silicon source has a total content of Fe, Al, Ca and Mg of 4000 mass ppm or less. Tm-500℃ ≦ Ta < Tm (1) Tm ≦ Tb < Tm + 200℃ (2)
[0008] The above manufacturing method includes a first step of obtaining a calcined product at Ta [°C] that satisfies the above formula (1). Here, since the total content of Fe, Al, Ca, and Mg in the silicon source contained in the raw material powder is sufficiently low, it is possible to prevent the crystallization or melting temperature of the silicon source from becoming low. Therefore, by heating at a temperature Ta that satisfies formula (1) in the first step, the reaction of producing silicon nitride from the raw material powder is promoted. Here, since the temperature Ta is lower than the coalescence temperature Tm, it is possible to suppress the coalescence (fusion) of the silicon source and to suppress the raw material components from being left unreacted inside the silicon nitride particles. Therefore, it is possible to suppress the components derived from the raw material components from remaining as impurities in the silicon nitride particles while proceeding with the production of silicon nitride.
[0009] In the second step, heating is performed at a temperature Tb that satisfies formula (2) for a predetermined time or less, which promotes the formation of silicon nitride from the remaining raw material components and suppresses the raw material components from remaining in the sintered product, while suppressing excessive clumping of the sintered product. Such a sintered product is easy to crush and has excellent sinterability. As described above, by heating the silicon nitride powder in multiple steps, including the first step of heating at a temperature Ta and the second step of heating at a temperature Tb, it is possible to produce a silicon nitride powder that can be used to produce a silicon nitride sintered body that combines high thermal conductivity and excellent high-temperature strength.
[0010] In the present disclosure, the "coalescence temperature Tm" refers to the temperature at which the amorphous material becomes crystalline (crystallization temperature) when the silicon source contains an amorphous material, and refers to the melting point when the silicon source is crystalline. For example, when the silicon source is silica containing an amorphous material, the coalescence temperature Tm is the temperature at which the amorphous material crystallizes. For example, when the silicon source is crystalline silica or metallic silicon, the coalescence temperature Tm is the melting point.
[0011] The raw material powder may contain silica powder and carbon powder as silicon sources, and the temperature Ta in the first step may be 1350 to 1480° C., and the temperature Tb in the second step may be 1500 to 1550° C. This makes it possible to produce silicon nitride powder with few impurities and suppressed agglomeration at low production costs.
[0012] The above manufacturing method may include a third step of obtaining silicon nitride powder from the fired product obtained in the second step. The silicon nitride powder obtained in the third step may contain silicon nitride as a main component, and may have a total oxygen content of 1.1 mass% or less, a surface oxygen content of 0.6 mass% or less, and a total fluorine and chlorine content of 25 mass ppm or less. By using such silicon nitride powder, a silicon nitride sintered body having excellent high-temperature strength and high thermal conductivity can be smoothly obtained.
[0013] The silicon nitride powder according to one aspect of the present disclosure contains silicon nitride as a main component, has a total oxygen content of 1.1 mass% or less, a surface oxygen content of 0.6 mass% or less, and a total fluorine and chlorine content of 25 mass ppm or less. Such silicon nitride powder has a sufficiently low content of oxygen, fluorine, and chlorine, which affect high-temperature strength. In addition, since the surface oxygen content is sufficiently low, oxides that precipitate at grain boundaries when a silicon nitride sintered body is produced can be reduced. Therefore, a silicon nitride sintered body having excellent high-temperature strength and high thermal conductivity can be obtained.
[0014] In this disclosure, the total oxygen content is the ratio of the mass of oxygen to the total mass of the silicon nitride powder. On the other hand, the surface oxygen content is the ratio of the mass of oxygen on the surface to the total mass of the silicon nitride powder. Also, the internal oxygen content is the ratio of the mass of oxygen inside to the total mass of the silicon nitride powder. Therefore, the following formula is established. Total oxygen content (mass%) = Internal oxygen content (mass%) + Surface oxygen content (mass%)
[0015] The alpha-phase ratio of the silicon nitride powder is preferably 95% by mass or more. A high alpha-phase ratio can promote grain growth during sintering of the silicon nitride powder. This allows a sufficiently dense silicon nitride sintered body to be produced. Therefore, a silicon nitride sintered body having even better high-temperature strength and high thermal conductivity can be obtained.
[0016] A method for producing a silicon nitride sintered body according to one aspect of the present disclosure includes a sintering step of sintering silicon nitride powder obtained by any one of the above-mentioned production methods to obtain a silicon nitride sintered body. In this production method, silicon nitride powder with reduced impurities and suppressed agglomeration is sintered, so that a sufficiently densified silicon nitride sintered body having excellent high-temperature strength and high thermal conductivity can be produced.
[0017] A method for producing a silicon nitride sintered body according to one aspect of the present disclosure includes a sintering step of sintering any of the silicon nitride powders described above to obtain a silicon nitride sintered body. In this production method, silicon nitride powder with reduced impurities is sintered, so that a silicon nitride sintered body having excellent high-temperature strength and high thermal conductivity can be produced. Effect of the Invention
[0018] According to the present disclosure, it is possible to provide a silicon nitride powder capable of producing a silicon nitride sintered body having both high thermal conductivity and excellent high-temperature strength by reducing impurities. It is also possible to provide a method for producing a silicon nitride powder capable of producing such a silicon nitride powder. It is also possible to provide a method for producing a silicon nitride sintered body capable of producing a silicon nitride sintered body having both high thermal conductivity and excellent high-temperature strength. [Brief description of the drawings]
[0019] [Figure 1] FIG. 1 is a diagram showing an example of an oxygen / nitrogen analysis chart. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Hereinafter, an embodiment of the present disclosure will be described. However, the following embodiments are examples for explaining the present disclosure, and are not intended to limit the present disclosure to the following contents.
[0021] [Method for producing silicon nitride powder] A method for producing silicon nitride powder according to an embodiment includes a first step of heating a raw material powder containing a silicon source at a temperature Ta [°C] that satisfies the following formula (1) for 50 hours or more to obtain a calcined product containing silicon nitride, where the coalescence temperature of the silicon source is Tm [°C]; a second step of heating the calcined product at a temperature Tb [°C] that satisfies the following formula (2) for 20 hours or less to obtain a fired product having a higher silicon nitride content than the calcined product; and a third step of obtaining silicon nitride powder from the fired product.
[0022] Tm - 500°C ≤ Ta < Tm (1) Tm ≤ Tb < Tm + 200°C (2)
[0023] From the viewpoint of sufficiently promoting the formation of silicon nitride in the first step, Ta may satisfy Tm - 300°C ≤ Ta, or may satisfy Tm - 150°C ≤ Ta. From the same viewpoint, the heating time at the temperature Ta in the first step may be 70 hours or more, or may be 90 hours or more. On the other hand, from the viewpoint of sufficiently suppressing the silicon source from coalescing (fusing) and leaving unreacted raw material components inside the silicon nitride particles, Ta may satisfy Ta < Tm - 30°C, or may satisfy Ta < Tm - 100°C. From the same viewpoint, the heating time at the temperature Ta in the first step may be 200 hours or less, or may be 150 hours or less.
[0024] From the perspective of reacting the raw materials remaining in the second step to sufficiently produce silicon nitride, Tm + 30°C ≤ Tb may hold, or Tm + 50°C ≤ Tb may also hold. From a similar perspective, the heating time at the temperature Tb [°C] in the second step may be 3 hours or more, or may be 5 hours or more. On the other hand, from the perspective of suppressing the agglomeration of the produced silicon nitride particles, Tb < Tm + 150°C may hold, or Tb < Tm + 100°C may also hold. From a similar perspective, the heating time at the temperature Tb [°C] may be 15 hours or less, or may be 12 hours or less.
[0025] In the manufacturing method of this embodiment, it has a first step of heating the raw material powder at a temperature Ta lower than the sintering temperature Tm, and a step of heating at a temperature Tb equal to or higher than the sintering temperature Tm. By performing such two-step heating, reduction of impurities is achieved, and silicon nitride powder with suppressed agglomeration can be manufactured. Such silicon nitride powder is suitable for silicon nitride sintered bodies because it can produce silicon nitride sintered bodies having high thermal conductivity and excellent high-temperature strength.
[0026] The difference between the temperature Ta and the temperature Tb (Tb - Ta) may be 20 to 300°C, may be 30 to 250°C, or may be 40 to 200°C from the perspective of achieving both sufficient reduction of impurities inside the silicon nitride particles and suppression of agglomeration at a high level. When the temperature Ta and the temperature Tb are not constant and vary within the ranges of the above formulas (1) and (2), it is sufficient if the difference between the average value of the temperature Ta and the average value of the temperature Tb is within the above range.
[0027] The silicon source may be amorphous silica powder or may be crystalline metal silica powder. The total content of Fe, Al, Ca, and Mg in the silicon source is 4000 mass ppm or less. Since the total content is sufficiently low, it is possible to suppress a decrease in the crystallization temperature or melting temperature of the silicon source. The total content of Fe, Al, Ca, and Mg in the silicon source may be 3000 mass ppm or less, may be 2000 mass ppm or less, or may be 1000 mass ppm or less from the perspective of sufficiently promoting the silicon nitride formation reaction in the first step.
[0028] <Example of using silica powder> Hereinafter, the case where the silicon source is silica powder will be described. The raw material powder may contain silica powder and carbon powder. In this case, silicon nitride can be produced by carbon reduction. The raw material powder may contain seed crystals of silicon nitride. Examples of silica powder include amorphous silica powder and crystalline silica powder. Examples of carbon powder include acetylene black, furnace black, channel black, and graphite. From the viewpoint of increasing sinterability, the silicon nitride used as the seed crystals preferably has a high alpha conversion rate (for example, an alpha conversion rate of 90 mass% or more).
[0029] The blending ratio of the carbon powder needs to be a predetermined ratio or more in order to reduce the silica powder. However, if the carbon powder is excessive, the amount of Si to react with fluorine and chlorine decreases, and the fluorine and chlorine contents of the silicon nitride powder tend to increase. The blending ratio of the carbon powder to the silica powder may be 2.0 to 3.8, or may be 3.0 to 3.7 on a molar basis (C / SiO2), from the viewpoint of obtaining a silicon nitride powder in which the total content of fluorine and chlorine and the total amount of oxygen are sufficiently reduced. The blending amount of the silicon nitride seed crystals to 100 parts by mass of the silica powder may be 10 to 20 parts by mass, or may be 11 to 18 parts by mass, from the viewpoint of obtaining a silicon nitride powder with a sufficiently high purity while reducing the production cost.
[0030] The total content of fluorine and chlorine in the raw material powder is preferably 50 mass ppm or less, more preferably 40 mass ppm or less, from the viewpoint of sufficiently reducing the total content of fluorine and chlorine in the silicon nitride powder produced. On the other hand, the total content of fluorine and chlorine in the raw material powder may be 10 mass ppm or more, or may be 20 mass ppm or more, from the viewpoint of reducing the production cost of the silicon nitride powder.
[0031] When the silicon source is amorphous silica powder, the coalescence temperature Tm is, for example, 1450°C or higher. The temperature Ta in the first step is preferably 1350 to 1450°C, more preferably 1370 to 1420°C. When the silicon source is crystalline silica powder, the coalescence temperature Tm is, for example, 1700°C or higher. In this case, the temperature Ta is preferably 1400 to 1500°C, more preferably 1430 to 1480°C.
[0032] By heating the raw material powder at such a temperature Ta, it is possible to sufficiently suppress the silicon source from coalescing (fusing) and leaving the raw material components unreacted inside the silicon nitride particles while allowing the formation of silicon nitride by the carboreduction method to proceed sufficiently. In addition, although the partial pressure of CO is high at the beginning of heating, by heating at a temperature Ta lower than the coalescence temperature Tm, it is possible to suppress the by-production of SiC.
[0033] When the silicon source is amorphous silica powder, the temperature Tb in the second step is preferably 1480 to 1530° C. When the silicon source is crystalline silica powder, the temperature Tb in the second step is preferably 1500 to 1550° C. By heating the calcined product at such a temperature Tb, the production of silicon nitride by the carboreduction method can be sufficiently promoted, and agglomeration of the calcined product containing silicon nitride can be sufficiently suppressed.
[0034] In the first and second steps, the raw material powder and the calcined product are heated, for example, using an electric furnace, and the reaction proceeds as shown in reaction formula (3) below. As the heating temperature increases, SiO2 and CO tend to react to produce SiC. In this example, although the temperature Tb is higher than the temperature Ta, the partial pressure of CO in the second step tends to be lower than in the first step, so the by-production of SiC can be suppressed. 3SiO2+6C+2N2→Si3N4+6CO↑ (3)
[0035] The first and second steps may be carried out in a nitrogen atmosphere. The oxygen concentration in the nitrogen atmosphere may be 100 ppm by volume or less, or may be 20 ppm by volume or less. By sufficiently lowering the oxygen concentration in the nitrogen atmosphere, the total oxygen content of the sintered product containing silicon nitride can be further reduced. In the third step of obtaining silicon nitride powder from the sintered product obtained in the second step, the sintered product obtained in the second step can be crushed to obtain silicon nitride powder. When the silicon nitride powder contains carbon or carbide, decarburization may be carried out before or after crushing. Decarburization can be carried out, for example, by heating the silicon nitride powder to 650 to 900°C in the air. This allows the total content of carbon and carbide in the silicon nitride powder to be reduced.
[0036] <Example of using silicon powder> Next, the case where the silicon source is silicon powder will be described below. The oxygen concentration in the silicon powder is preferably 0.4 mass% or less. Before the first step, a pretreatment step using a pretreatment liquid containing hydrofluoric acid may be performed to reduce the oxygen concentration in the silicon powder. The first and second steps are performed in a mixed atmosphere containing nitrogen and at least one selected from the group consisting of hydrogen and ammonia. In this way, boron nitride powder can be obtained by the so-called direct nitridation method.
[0037] When the silicon source is silicon powder, the coalescence temperature Tm is the melting point of the silicon powder since the silicon powder is crystalline. Therefore, the coalescence temperature Tm is about 1414°C. The temperature Ta in the first step is preferably 1050 to 1350°C. By heating the raw material powder at such a temperature Ta, it is possible to sufficiently advance the production of silicon nitride by the direct nitriding method, while sufficiently suppressing the silicon powder from coalescing (fusing) and leaving the raw material components unreacted inside the silicon nitride particles.
[0038] When the silicon source is silicon powder, the temperature Tb in the second step is preferably 1420 to 1550° C., more preferably 1450 to 1500° C. By heating the calcined product at such a temperature Tb, the formation of silicon nitride by the direct nitriding method can be sufficiently promoted, and the agglomeration of the silicon nitride powder can be sufficiently suppressed. In addition, by carrying out the first step at a temperature Ta lower than the temperature Tb in the second step, the formation of β-silicon nitride can be suppressed, and the proportion of α-silicon nitride can be increased.
[0039] In the first and second steps, the raw material powder and the calcined product are heated in a mixed atmosphere containing at least one selected from the group consisting of nitrogen, hydrogen, and ammonia to obtain a calcined product having a higher silicon nitride content than the calcined product. The total content of hydrogen and ammonia in the mixed atmosphere may be 10 to 40 volume %.
[0040] When the fired product obtained in the second step is in the form of an ingot, a step of pulverizing the fired product to obtain silicon nitride powder may be carried out. The pulverization may be carried out in multiple stages, including coarse pulverization and fine pulverization. The pulverization may be carried out in a wet manner using, for example, a ball mill. Silicon nitride has a specific surface area of 8.0 to 15.0 m 2 It may be ground to a concentration of 1 / g.
[0041] The silicon nitride powder obtained by pulverization may be mixed with hydrofluoric acid having a hydrogen fluoride concentration of 10 to 40 mass % to dissolve and remove impurities. The hydrogen fluoride concentration in the hydrofluoric acid may be 12 to 30 mass %. The temperature of the hydrofluoric acid may be, for example, 40 to 80°C. The time for immersing the silicon nitride powder in hydrofluoric acid may be, for example, 1 to 10 hours.
[0042] According to the manufacturing method of the present embodiment, it is possible to sufficiently reduce impurities derived from raw material components remaining inside silicon nitride particles while suppressing agglomeration. By using the silicon nitride powder obtained by such a manufacturing method, it is possible to manufacture a silicon nitride sintered body having both high thermal conductivity and excellent high-temperature strength.
[0043] In the above examples, the case where crystalline or amorphous silica is used as the silicon source and the case where crystalline silicon powder is used are described, but the silicon source is not limited to these. Note that multiple types of substances may be used as the silicon source. In this case, the coalescence temperature is additive. In other words, the coalescence temperature when amorphous silica and crystalline silica are used in combination in a mass ratio of 1:1 as the silicon source is calculated by the following formula (4). Tm = Tx x 0.5 + Ty x 0.5 (4) In the above formula (4), Tx is the crystallization temperature of amorphous silica (°C), and Ty is the melting point of crystalline silica (°C).
[0044] [Silicon nitride powder] The silicon nitride powder according to one embodiment contains silicon nitride as a main component, has a total oxygen content of 1.1 mass% or less, a surface oxygen content of 0.6 mass% or less, and a total content of fluorine and chlorine of 25 mass ppm or less. The silicon nitride content in the silicon nitride powder may be, for example, 88 mass% or more, 90 mass% or more, or 92 mass% or more.
[0045] The total oxygen content may be 1.0 mass% or less, or 0.9 mass% or less, from the viewpoint of being able to produce a silicon nitride sintered body having even better high-temperature strength and high thermal conductivity. By reducing the total oxygen content of the silicon nitride powder, it is possible to reduce internal defects in the silicon nitride sintered body obtained by sintering the silicon nitride powder. From the same viewpoint, the internal oxygen content may be 0.9 mass% or less, or 0.8 mass% or less.
[0046] From the viewpoint of reducing the production cost of the silicon nitride powder, the total oxygen content may be 0.1 mass% or more, or may be 0.5 mass% or more. For example, the total oxygen content of the silicon nitride powder may be 0.1 to 1.1 mass%, or may be 0.5 to 0.9 mass%.
[0047] From the viewpoint of enabling the production of a silicon nitride sintered body having even superior high-temperature strength and high thermal conductivity, the surface oxygen content may be 0.5 mass % or less, or may be 0.4 mass % or less. By reducing the surface oxygen content of the silicon nitride powder, it is possible to reduce oxides that precipitate at the grain boundaries of the silicon nitride sintered body obtained by sintering the silicon nitride powder.
[0048] From the viewpoint of reducing the production cost of the silicon nitride powder, the surface oxygen content may be 0.1 mass% or more, or may be 0.2 mass% or more. The total oxygen content of the silicon nitride powder may be, for example, 0.1 to 0.6 mass%, or may be 0.2 to 0.5 mass%.
[0049] The total oxygen content, surface oxygen content, and internal oxygen content of silicon nitride powder can be measured using a commercially available oxygen / nitrogen analyzer. Measurements are performed by continuously heating the silicon nitride powder from 20°C to 2400°C at a heating rate of 8°C / sec in a helium gas atmosphere. The oxygen content can be quantified from the area of the peak resulting from oxygen desorption from the obtained measurement results.
[0050] FIG. 1 is an example of a chart obtained by oxygen and nitrogen analysis of silicon nitride powder. Peak 1 is the surface oxygen peak, and peak 2 is the internal oxygen peak. Peak 3 is the nitrogen peak. Line 4 shows the temperature rise line. Peak 1 and peak 2 are divided by temperature T1 at which silicon nitride decomposes and nitrogen begins to be generated. Temperature T1 is the temperature at which detection of peak 3 begins, and is usually between 1350 and 1500 ° C. The temperature at which detection of peak 1 begins (the temperature at the left end of peak 1) is, for example, 750 to 1200 ° C. The temperature at which detection of peak 2 ends (the temperature at the right end of peak 2) is, for example, 1600 to 1800 ° C. From the integrated values (areas) of peaks 1 and 2, the amount of internal oxygen and the amount of surface oxygen can be calculated based on the calibration curve. The sum of the amount of internal oxygen and the amount of surface oxygen is the total amount of oxygen.
[0051] In FIG. 1, the left end of peak 3 (temperature T1) coincides with the deepest part of the valley of peaks 1 and 2, but these do not have to coincide completely. However, normally, temperature T1 (the left end of peak 3) will be located between the temperatures at which the tops of peaks 1 and 2 are detected. In FIG. 1, the integrated value of peak 2 is greater than the integrated value of peak 1, but this relationship is not limiting. For example, the integrated value of peak 1 may be greater than the integrated value of peak 2.
[0052] The total content of fluorine and chlorine in the silicon nitride powder may be 20 mass ppm or less, or 15 mass ppm or less, from the viewpoint of being able to produce a silicon nitride sintered body having even better high-temperature strength. By reducing the total content of fluorine and chlorine in the silicon nitride powder, the fluorine and chlorine contained in the grain boundary phase of the silicon nitride sintered body obtained by sintering the silicon nitride powder is reduced. Therefore, the grain boundary phase of the silicon nitride sintered body can be suppressed from softening at high temperatures. Therefore, it is possible to obtain a silicon nitride sintered body having sufficiently high high-temperature strength. The total content of fluorine and chlorine tends to depend on the purity of the starting material used in producing the silicon nitride powder, the blending ratio of the raw materials, the heating conditions, etc.
[0053] For example, when producing silicon nitride powder by a carbon reduction method using silica powder as a silicon source, if the compounding ratio of silica powder to carbon powder (C / SiO2) is too small, the elimination of SiCl4 due to the reaction of SiO2 or SiO with Cl tends to be difficult to proceed. The same tendency also occurs when the heating time is too short.
[0054] The total content of fluorine and chlorine in the silicon nitride powder may be 1 mass ppm or more, or may be 3 mass ppm or more, from the viewpoint of reducing the manufacturing cost of the silicon nitride powder. The total content of fluorine and chlorine in the silicon nitride powder may be, for example, 1 to 25 mass ppm, or may be 3 to 20 mass ppm. The total content of fluorine and chlorine in the silicon nitride powder can be measured by heating the silicon nitride powder and quantifying the fluorine and chlorine contained in the generated gas by ion chromatography.
[0055] The alpha-phase rate of the silicon nitride powder is preferably 95% by mass or more. A high alpha-phase rate can promote grain growth during sintering of the silicon nitride powder. This allows a sufficiently dense silicon nitride sintered body to be produced. Therefore, a silicon nitride sintered body having even better high-temperature strength and high thermal conductivity can be obtained.
[0056] The alpha-phase ratio of the silicon nitride powder may be 99% by mass or less, or 98% by mass or less, from the viewpoint of reducing the manufacturing cost of the silicon nitride powder. An example of the alpha-phase ratio of the silicon nitride powder may be 93 to 99% by mass. The alpha-phase ratio of the silicon nitride powder can be determined based on the diffraction line intensity of X-ray diffraction.
[0057] The silicon nitride powder may contain carbon or carbide as a component other than silicon nitride. The total content of carbon and carbide in the silicon nitride powder is preferably 10 mass% or less, more preferably 7 mass% or less, calculated as carbon.
[0058] The silicon nitride powder according to this embodiment has a sufficiently low content of oxygen, fluorine, and chlorine, which affect high-temperature strength. In addition, since the surface oxygen content is sufficiently low, oxides that precipitate at grain boundaries when the silicon nitride sintered body is produced can be reduced. Therefore, a silicon nitride sintered body having excellent high-temperature strength and high thermal conductivity can be obtained. Such silicon nitride powder can be produced by the above-mentioned production method. However, the production method is not limited to the above-mentioned one.
[0059] The method for producing a silicon nitride sintered body according to one embodiment includes a sintering step of sintering the silicon nitride powder or the silicon nitride powder obtained by the above-mentioned production method to obtain a silicon nitride sintered body. In this production method, for example, the silicon nitride powder is pressed at a molding pressure of, for example, 3.0 to 10.0 MPa to obtain a molded body. The molded body may be produced by uniaxial pressing or by CIP. Also, the molded body may be sintered while being molded by hot pressing.
[0060] The sintering of the molded body may be carried out in an inert gas atmosphere such as nitrogen gas or argon gas. The pressure during sintering may be 0.7 to 0.9 MPa. The sintering temperature may be 1700 to 1900°C. The sintering time at the sintering temperature may be 4 to 20 hours, or 8 to 16 hours. The rate of temperature rise to the sintering temperature may be, for example, 1.0 to 10.0°C / hour.
[0061] The silicon nitride sintered body thus obtained has a sufficiently reduced total oxygen content, surface oxygen content, and total fluorine and chlorine content. Since the oxygen content is sufficiently reduced, defects inside the silicon nitride sintered body and oxides precipitated at grain boundaries can be suppressed. Therefore, it has excellent high-temperature strength as well as insulation and thermal conductivity. Defects contained in the silicon nitride sintered body include lattice defects such as dislocations and pores. In addition, since the total content of fluorine and chlorine is sufficiently reduced, it is possible to suppress softening of the grain boundary phase of the silicon nitride sintered body at high temperatures. Therefore, a silicon nitride sintered body having sufficiently high high-temperature strength can be obtained.
[0062] In the present disclosure, high-temperature strength refers to strength at 1300°C. A silicon nitride sintered body having high strength in such a temperature range can be particularly suitably used for applications such as gas turbines, power modules for automobiles, and bearings. The bending strength of the silicon nitride sintered body according to one embodiment at a temperature of 1300°C may be, for example, 700 MPa or more, or may be 750 MPa or more. This strength is a four-point bending strength (1300°C) measured using a commercially available measuring device.
[0063] Although several embodiments have been described above, the present disclosure is not limited to the above-mentioned embodiments. For example, the silicon nitride powder may be used for purposes other than the manufacture of silicon nitride sintered bodies. In addition, the temperature Ta in the first step and the temperature Tb in the second step do not necessarily need to be constant, and may vary within a predetermined range, and the temperature may be changed continuously or stepwise within a predetermined range. The silicon source is not limited to silica powder and silicon powder. For example, a crystalline or amorphous silicate compound may be used instead of silica powder. In that case, the conditions of the first step and the second step may be the same as those of the example using silica powder. EXAMPLES
[0064] The present disclosure will be described in more detail with reference to examples and comparative examples, but the present disclosure is not limited to the following examples.
[0065] <Preparation of silicon nitride powder> Example 1 A raw powder was prepared by blending crystalline silica powder (average particle size: 5 μm), acetylene black powder, and silicon nitride powder (seed crystals). The coalescence temperature Tm of this silica powder was 1700° C., which was its melting point. The total content of Fe, Al, Ca, and Mg in the silica powder was 580 ppm by mass. This total content was measured using an ICP emission spectrometer. The total content of fluorine and chlorine in the raw powder was 40 ppm by mass. The blending ratio (mass basis) was silica powder: acetylene black powder: silicon nitride powder = 55.2%: 38.5%: 6.3%. The molar ratio of acetylene black to silica powder (C / SiO2) was 3.5. 320 g of this raw powder was filled into a 2 L polyethylene container, silicon nitride balls (φ: 15 mm) were added, and the mixture was mixed in a ball mill for 2 hours.
[0066] The raw material powder was heated in an electric furnace at atmospheric pressure in a nitrogen atmosphere at 1450°C (temperature Ta) for 50 hours to obtain a calcined product (first step). After 50 hours, the temperature was increased using the same electric furnace and heated in a nitrogen atmosphere at 1520°C (temperature Tb) for 10 hours (second step). The oxygen concentration in the nitrogen atmosphere in the first and second steps was 110 volume ppm or less. The obtained calcined product was crushed in a mortar made of silicon nitride to obtain a nitride powder. This was placed in an alumina crucible and heated in an electric furnace at 800°C for 3 hours to decarburize. The decarburized powder obtained by decarburization was filled into an alumina pot together with silicon nitride balls and pulverized in a vibration mill for 3 hours to obtain a silicon nitride powder. Table 1 shows the type of silicon source, the coalescence temperature, the impurity content, the molar ratio of C / SiO2, and the heating conditions.
[0067] Example 2 Silicon nitride powder was obtained in the same manner as in Example 1, except that amorphous fused silica powder (average particle size: 0.6 μm) was used, the temperature Ta in the first step was 1400° C., and the heating time at the temperature Ta was 100 hours. The temperature at which the fused silica powder crystallizes is 1450° C., so the coalescence temperature Tm is 1450° C. The total content of Fe, Al, Ca, and Mg in the silica powder was 473 ppm by mass. The total content of fluorine and chlorine in the raw material powder was 40 ppm by mass. Table 1 shows the type of silicon source, coalescence temperature, impurity content, molar ratio of C / SiO2, and heating conditions.
[0068] Comparative Example 1 The raw material powder prepared in Example 1 was heated in one step, not in two steps. That is, the raw material powder was heated in an electric furnace at 1500°C for 60 hours in a nitrogen atmosphere at atmospheric pressure. In this way, silicon nitride powder was obtained in the same manner as in Example 1, except that the raw material powder was heated in one step. Table 1 shows the type of silicon source, the coalescence temperature, the impurity content, the molar ratio of C / SiO2, and the heating conditions.
[0069] Comparative Example 2 Silicon nitride powder was obtained in the same manner as in Comparative Example 1, except that the blending ratio (mass basis) in preparing the raw material powder was crystalline silica powder: acetylene black powder: silicon nitride powder = 52.3%: 41.7%: 6.0%. The molar ratio of acetylene black to crystalline silica powder (C / SiO2) was 4.0. Table 1 shows the type of silicon source, coalescence temperature, impurity content, C / SiO2 molar ratio, and heating conditions.
[0070] Comparative Example 3 The raw material powder prepared in Example 1 was heated in one step, not in two steps. That is, the raw material powder was heated in an electric furnace in a nitrogen atmosphere at atmospheric pressure at 1450°C for 20 hours. In this way, silicon nitride powder was obtained in the same manner as in Example 1, except that the raw material powder was heated in one step. Table 1 shows the type of silicon source, coalescence temperature, impurity content, C / SiO2 molar ratio, and heating conditions.
[0071] [Table 1]
[0072] <Evaluation of silicon nitride powder> The oxygen content in the silicon nitride powder of each example and comparative example was measured by the following procedure. 0.01 g of silicon nitride powder and 0.01 g of carbon powder were set in an oxygen / nitrogen analyzer (manufactured by Horiba, Ltd., device name: EMGA-920W). In a helium gas atmosphere, the temperature was raised from 20°C to 2400°C at a heating rate of 8°C / sec. Oxygen and nitrogen generated with the temperature rise were detected. As a result, a peak indicating the desorption of oxygen was obtained as shown in FIG. 1. The surface oxygen amount and the internal oxygen amount were calculated from the respective peak areas resulting from the desorption of surface oxygen and internal oxygen. In addition, the total oxygen amount was calculated based on the sum of these values. The measurement results of the total oxygen amount and the surface oxygen amount were as shown in Table 2.
[0073] The total content of fluorine and chlorine contained in the silicon nitride powder was measured by the following procedure. The silicon nitride powder was heated using an automatic sample combustion device (manufactured by Mitsubishi Chemical Corporation, device name: AQF-2100H type), and the generated gas was dissolved in water. The fluorine and chlorine dissolved in water were measured using an ion chromatograph (manufactured by Thermo Fisher Scientific, device name: ICS-2100) in accordance with JIS R 1603:2007. Based on this measured value, the fluorine and chlorine contained in the silicon nitride powder were quantified. The measurement results are shown in Table 2. In Table 2, "amount of halogen" refers to the total content of fluorine and chlorine.
[0074] The alpha phase ratio of the prepared silicon nitride powder was measured by the following procedure. X-ray diffraction of the silicon nitride powder was performed using an X-ray diffractometer (Rigaku Corporation, device name: Ultima IV) with CuKα radiation. The alpha phase was determined by the diffraction intensity I a102 and the (210) diffraction intensity I a210 , β phase has a diffraction intensity of I b101 and the (210) diffraction intensity I b210 Using these diffraction line intensities, the gelatinization rate was calculated according to the following formula. The results are shown in Table 2. Alpha conversion rate (mass%) = [(I a102 +I a210 ) / (I a102 +I a210 +I b101 +I b210 )] x 100
[0075] <Preparation of sintered silicon nitride> The silicon nitride powders of each Example and Comparative Example were each uniaxially pressed to produce a cylindrical molded body. The molded body was placed in an electric furnace equipped with a carbon heater and heated to 1850°C in a nitrogen atmosphere. After sintering at 1850°C for 6 hours, the body was cooled to obtain a silicon nitride sintered body.
[0076] <Evaluation of sintered silicon nitride> The density, four-point bending strength at 1300°C, and thermal conductivity of the obtained silicon nitride sintered body were measured. The density was measured by the Archimedes method, and the four-point bending strength at 1300°C was measured using an autograph AG-2000 (product name) manufactured by Shimadzu Corporation. The results are shown in Table 2 as relative values with the measurement results of Example 1 as the standard.
[0077] The silicon nitride sintered body was ground to prepare a disk of 10 mmφ×3 mm for measuring thermal conductivity. Thermal diffusivity and specific heat capacity were measured by the laser flash method (based on JIS R1611), and the product of density, thermal diffusivity, and specific heat capacity of the sintered body was calculated to obtain the thermal conductivity at room temperature. The results are shown in Table 2 as relative values based on the measurement results of Example 1.
[0078] [Table 2]
[0079] In Examples 1 and 2, in which heating was performed in two stages at the prescribed temperatures Ta and Tb, silicon nitride powder was obtained in which the total oxygen content, surface oxygen content, and halogen content were sufficiently reduced. The silicon nitride sintered body produced using such silicon nitride powder was sufficiently densified and had excellent high-temperature strength and high thermal conductivity. [Industrial Applicability]
[0080] According to the present disclosure, there is provided a silicon nitride powder capable of producing a silicon nitride sintered body having both high thermal conductivity and excellent high-temperature strength. Also, there is provided a method for producing a silicon nitride powder capable of producing such a silicon nitride powder. Also, there is provided a method for producing a silicon nitride sintered body capable of producing a silicon nitride sintered body having both high thermal conductivity and excellent high-temperature strength.
Claims
1. A method for producing a silicon nitride powder using a raw material powder containing a silicon source, comprising: a first step of heating the raw material powder for 50 hours or more at a temperature Ta [°C] that satisfies the following formula (1), where Tm [°C] is the coalescence temperature of the silicon source, to obtain a calcined product containing silicon nitride; A second step of heating the calcined product at a temperature Tb [°C] that satisfies the following formula (2) for 20 hours or less to obtain a calcined product containing silicon nitride, A method for producing a silicon nitride powder, wherein the silicon source has a total content of Fe, Al, Ca and Mg of 4000 ppm by mass or less. Tm-500℃ ≦ Ta < Tm (1) Tm≦Tb<Tm+200℃ (2)
2. The raw material powder contains silica powder as the silicon source and carbon powder, The temperature Ta in the first step is 1350 to 1480° C., 2. The method for producing silicon nitride powder according to claim 1, wherein the temperature Tb in the second step is 1500 to 1550°C.
3. A third step of obtaining silicon nitride powder from the fired product obtained in the second step, 3. The method for producing a silicon nitride powder according to claim 1, wherein the silicon nitride powder contains silicon nitride as a main component, has a total oxygen content of 1.1 mass% or less, a surface oxygen content of 0.6 mass% or less, and a total fluorine and chlorine content of 25 mass ppm or less.
4. It contains silicon nitride as its main component. The total oxygen content is 0.9% by mass or less, the surface oxygen content is 0.2% by mass or less, and the total content of fluorine and chlorine is 25 ppm by mass or less, A silicon nitride powder having an alpha conversion rate of 95 to 99 mass %.
5. The silicon nitride powder according to claim 4, wherein the total content of fluorine and chlorine is 3 to 15 ppm by mass.
6. A method for producing a silicon nitride sintered body, comprising a sintering step of firing the silicon nitride powder obtained by the method according to any one of claims 1 to 3 to obtain a silicon nitride sintered body.
7. A method for producing a silicon nitride sintered body, comprising a sintering step of sintering the silicon nitride powder according to claim 4 or 5 to obtain a silicon nitride sintered body.
Citation Information
Patent Citations
Removal of chlorine and / or fluorine from silicon nitride powder
JP1987143805A
Production of high alpha-type silicon nitride
JP1995081910A
Silicon nitride powder and its production
JP1995206409A
Silicon nitride powder
JP1996012306A
Silicon nitride powder
JP2000302421A